2013
DOI: 10.1371/journal.pone.0062712
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Abundance of Antibiotics and Resistance Genes in Rivers, Canal and near Drug Formulation Facilities – A Study in Pakistan

Abstract: Antibiotic resistance (AR) is a global phenomenon that has severe epidemiological ramifications world-wide. It has been suggested that antibiotics that have been discharged into the natural aquatic environments after usage or manufacture can promote the occurrence of antibiotic resistance genes (ARG). These environmental ARGs could serve as a reservoir and be horizontally transferred to human-associated bacteria and thus contribute to AR proliferation. The aim of this study was to investigate the anthropogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(111 citation statements)
references
References 49 publications
3
103
4
1
Order By: Relevance
“…In general, it could be concluded that non-routine episodes associated with untreated effluents, landfills and medical wastewaters from urban inhabitants would exacerbate the pollution of antibiotics [33,34]. Furthermore, compared with previous studies, the mean CIP concentration for the water samples (169.2 ± 107.9 ng/L) was of similar levels to some other aquatic environments, such as the Wangyang River in China (205.5 ng/L) [35], Lebanese rivers (108 ng/L) [36], and the rivers in Northern Pakistan (110 ng/L) [37]. However, it was far greater than that in the water samples of Seine River (France) [38], Yangtze Estuary (China) [39], and Pearl River (China) [40], as well as other catchments in China (Poyang Lake, Chao Lake, and Liao River) [27,41,42].…”
Section: Antibiotics In the Water Phase Of The Hrdrmentioning
confidence: 51%
“…In general, it could be concluded that non-routine episodes associated with untreated effluents, landfills and medical wastewaters from urban inhabitants would exacerbate the pollution of antibiotics [33,34]. Furthermore, compared with previous studies, the mean CIP concentration for the water samples (169.2 ± 107.9 ng/L) was of similar levels to some other aquatic environments, such as the Wangyang River in China (205.5 ng/L) [35], Lebanese rivers (108 ng/L) [36], and the rivers in Northern Pakistan (110 ng/L) [37]. However, it was far greater than that in the water samples of Seine River (France) [38], Yangtze Estuary (China) [39], and Pearl River (China) [40], as well as other catchments in China (Poyang Lake, Chao Lake, and Liao River) [27,41,42].…”
Section: Antibiotics In the Water Phase Of The Hrdrmentioning
confidence: 51%
“…This is supported by many studies showing correlations between the dissemination and concentrations of antibiotic resistance genes and the use of antibiotics (2,8,9). It is generally accepted that bacteria readily lose their antibiotic resistance genes in the absence of selective pressures because, in most cases, antibiotic resistance is associated with reduced bacterial fitness due to a decrease in growth rate (41,42).…”
Section: Discussionmentioning
confidence: 89%
“…It is generally thought that the use of antibiotics as human and veterinary medicine or as animal feed additives is a major driving force in the development of antibioticresistant bacteria and the dissemination of antibiotic resistance genes (2)(3)(4). Indeed, high levels of antibiotic resistance genes have been identified in a variety of human-impacted milieus such as wastewater sludge, soils fertilized with manure, and river waters that have been frequently exposed to antibiotics (5)(6)(7)(8)(9). Surprisingly, however, many other studies have shown that the widespread occurrence of antibiotic resistance genes are sometimes unrelated to human activities.…”
mentioning
confidence: 99%
“…13 and 45). We used subinhibitory antibiotic concentrations, which the bacteria are most likely to encounter in natural settings and in host tissues (46)(47)(48)(49). We assessed (i) the impact of antibiotic pressure on the interaction between the two production genotypes and (ii) the consequences for the population response to antibiotics, in particular the evolution of resistance.…”
Section: Significancementioning
confidence: 99%